The Gap in Social Stratification in Mark Twain's Novel The Adventure of Huckleberry Finn based on Marxist Sociological Review - Muiz Yusron Hamdi (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
This research journal describes the Novel The Adventure of Huckleberry Finn (1885) by Mark Twain with a review of Marxist Sociology. This research focuses on the field of sociology of literature. The Adventure of Huckleberry Finn (1885) by Mark Twain tells the story of the adventures of Huck with his clever and brave character and his best friend, Jim. The story's atmosphere is set in the early era of America with the conditions of social problems at that time. This study analyzes the structure and social class based on the study of Marxism because the plot of the novel contains several narratives that describe social inequality, one of which describes slavery and racism, causing the impact of social class stratification. This study takes the primary data in the form of several descriptive narratives taken from the Novel The Adventure of Huckleberry Finn (1885) by Mark Twain. It analyzes through the Marxist Sociology approach initiated by Karl Marx, who divides society into two social classes, the bourgeois class and the proletarian class (upper class). Furthermore, lower class). The research method used is descriptive qualitative, it is research procedures that focus on descriptive data in writing or text. The analysis technique used is based on qualitative data analysis methods, with collecting data by reading and observing the narrative text in the novel, reducing data that is considered relevant to the issues raised, presenting data systematically and explaining it based on Marxist sociology studies and drawing conclusions from the data that has been explained in detail. Whole. The novel The Adventure of Huckleberry Finn (1885) even became a debate and received much criticism because it seemed to show racism in the narrative used.